Spin glass behavior in La0.7Ca0.23Sr0.07MnO3 nanofibers obtained by electrospinning - Burrola Gándara, Luis Andrés (2019)
This work contributes to the development of new nanostructured mixed valence manganites and to explore and optimize their magnetic properties at 1-D level. Nanofibers of La0.7Ca0.23Sr0.07MnO3 manganite were fabricated using the electrospinning method and three different heat treatments to determine how the nanostructure affects its thermomagnetic behavior. From scanning electron microscopy, nanofibers morphology was observed and average diameters of 75, 94, and 97 nm were identified after heat treatments of 973, 1073, and 1173 K, respectively. According to X-ray diffraction technique, a single-phase orthorhombic structure was defined for each sample. Average crystallite sizes were determined as 47, 49, and 58 nm. A ferromagnetic to paramagnetic transition with Curie temperatures of 297, 305, and 314 K were identified, respectively. Furthermore, a glassy state was induced by nanofibers agglomeration. The spin glass and irreversible temperatures diminished as the magnetic field was increased and a highly anisotropic state was evidenced for all samples. Thermomagnetic behavior in manganites showed to be significantly influenced by the one-dimensional structure and exposed how the dimensionality proportionated by the fabrication method can be used to adjust magnetic properties.